Seeing Beyond Diseases and Disorders: Symptom Complexes as Manifestations of Mental Constituents - Daker, Maurício V. (Frontiers in Psychiatry, 2018)
Many psychopathologists have approached symptom complexes without prejudging them as physical deficits or diseases, an approach suitable to connections with normal mind, to a broad dimensional and anthropological view of mental disorders. It contrasts with the prevailing orientation in psychiatry towards the medical model of delimited diseases. Discussions of this order centered on symptom complexes gained special prominence in psychiatry between the early 20th century through Alfred Hoche and World War II through Carl Schneider. Their works, in addition to the work of other authors of that period, are considered. The late Kraepelin conceded the possibility that affective and schizophrenic manifestations do not represent disease processes but rather represent areas of human personality. Seeing mind or persons is a paradigmatic different perspective than seeing diseases. Re-emerge in this comprehensive or integrationist context the notion of unitary psychosis and philosophical questions as the mind-body problem; as background there was a process metaphysics. The possibility of human experience in a phenomenological sense is considered, and a matrix of symptom or function complexes is related to it. Examples of past unitary models of mental disorders with their neurophysiologic explanations are given, as well as an analogy to current biological aspects of the endogenous in chronobiology. The question or hypothesis arises whether mental symptom complexes are manifestations of mind constituents or functions that make human experience and mind possible. The present work is a conceptual analysis that indicates a positive answer to this question. The expectation is to emphasize the perspectives of investigation in psychopathology and sciences of mind fostered by this view of symptom complexes.